Plan financiero de la empresa de eventos 1A y su impacto en la recreación en los últimos 5 años (2023)
In every company it is necessary to have a knowledge of the current finances and with it also of its previous finances, with this it is given to denote the financial stability that the company has, it is reached to understand in what current situation is the entity, with it we must also get to make effective and correct decisions for the entity. For this we must have and generate a financial analysis in which allows us to visualize the performance and stability of the company, since with this we can observe if we have any deficit, if we have any difficulty or see if we have good financial management of the company.